Divination and philosophy in the letters of Paul - Sharp, Matthew T. (Edinburgh Edinburgh University Press, 2022)
Studies the topic of divine communication in Paul's letters in the context of Graeco-Roman divination.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Hochschulschrift